Cytotoxicity Effects of Benalu Tea Extract (Scurrula oortina) on Hella cells - Kusumo Hariyadi; Fatmawati; Subandrate; Fahira Aninditia; Dazakiah (Biomedical Journal of Indonesia, 2020)
Tea garden waste has been investigated in the form of parasite tea Squrula oortina SpeciesFamily: Loranthaceae from the Dempo Pagar Alam tea plantation, Lahat Regency, South Sumatra.Stem and leaf samples are then dried and powdered, then isolated with 70% water-ethanolsubfraction. The extract was then dried by vacuum distillation at 70 o C until a concentrated extractwithout ethanol was obtained. The results of the study were tea parasite extract, and the extractwas tested for phytochemicals (monounsaturated fatty acids and double, theobromine derivates,quercetin derivates and Epicatekin derivates). Next, it would be taken to the Laboratory ofBiological Sciences at Gajah Mada University to be tested for cytotoxic effects on Hella cells,with control positive doxorubicin. The results of the research were tea leaves extract IC50 = 2538ug/mL and the standard of doxorubicin IC50 = 0.88 ug/mL so that it could be concluded that theparasite of the tea parasite had cytotoxic and proliferative effects.